The Effect of Working Capital, Sales, and Operating Expenses on Net Profit on Bengkel Sejahtera Motor Source Cirebon - muzayyanah, muzayyanah; Indriyani, Rinni; Tatmimah, Itat; Djadjuli, Mohamad (Jurnal Ekuisci, 2024)
. This study was driven by a decline in net profit at Bengkel Sejahtera Motor Sumber Cirebon during the 2019-2023 period. The reduction in net profit suggests that working capital has not been utilized optimally, and operational expenses have risen each year. Therefore, this research seeks to explore how workshop owners can maximize the use of their working capital and minimize operational costs effectively to boost net profit at Bengkel Sejahtera Motor Sumber Cirebon. The aim of this research is to analyze the influence of working capital, sales, and operational expenses on the net profit of the workshop. This study employs a quantitative approach, with a population of 144 financial data entries, and uses random sampling as the sampling method. The data analysis techniques applied include descriptive statistics, multiple linear regression analysis, and a series of data quality tests, such as validity tests, reliability tests, and classical assumption tests (normality, multicollinearity, and heteroscedasticity tests). Hypothesis testing is conducted using the t-test (partial) and F-test (simultaneous). The findings of this research reveal that working capital has a significant negative impact on net profit, sales have a significant positive effect, and operational costs exert a significant negative influence on net profit. Furthermore, working capital, sales, and operational costs together significantly affect the net profit.